Older Adults Living Alone in Thailand: Socioeconomic Inequality and Its Relation to Unmet Health Needs - Meemon, Natthani (Animo Repository, 2020)
This study aimed to investigate socioeconomic inequality and its relation to unmet health needs among older adults living alone in Thailand. Descriptive analyses with F-tests and chi-squared tests, and logistic regression analyses were conducted with the national health census 2017 data. The results indicated that older adults living alone, compared to those not living alone, had significantly low socioeconomic conditions and high unmet needs. They were more likely to be lower-income, older, female, lower-educated, unemployed, and chronically-ill people. Particularly for income, the proportion of people with income below the national poverty line among older adults living alone (38.75%) were almost two times and four times larger than those living with only one family (19.39%) and more than one families (10.98%), respectively. Additionally, we found that the residence type “living alone” and income were the most significant determinants for the unmet needs. Based on the results, we recommend that the government reinforce the current pension and community health volunteer programs. Particularly for the pension program, a simulation analysis that we conducted proposed that the current pension allowance (600–1,000 Baht) should be raised up to 3,500 Baht, which could substantially alleviate the unmet needs.